2005
DOI: 10.1111/j.1471-4159.2005.03095.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the neurofilament light gene linked to Charcot‐Marie‐Tooth disease cause defects in transport

Abstract: Neurofilament light gene mutations have been linked to a subset of patients with Charcot-Marie-Tooth disease, the most common inherited motor and sensory neuropathy. We have previously shown that Charcot-Marie-Tooth-linked mutant neurofilament light assembles abnormally in non-neuronal cells. In this study, we have characterized the effects of expression of mutant neurofilament light proteins on axonal transport in a neuronal cell culture model. We demonstrated that the Charcot-Marie-Tooth-linked neurofilament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 42 publications
6
75
0
5
Order By: Relevance
“…In previous studies, Pro22Ser and Pro22Thr mutants showed defects in filamentous network formation irregular aggregation in the SW13-cell, and the mutations abolish the Thr-Pro PDPK phosphorylation site in the NEFL head domain, which regulates filament assembly via phosphorylation (Pérez-Ollé et al 2005;Sasaki et al 2006). In our study, patients with the Pro22Arg mutation had the same demyelinating neuropathies as did patients with the Pro22Thr mutation; therefore, it seems that the Pro22Arg mutation also may abolish the Thr-Pro phosphorylation site of the head domain by PDPKs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In previous studies, Pro22Ser and Pro22Thr mutants showed defects in filamentous network formation irregular aggregation in the SW13-cell, and the mutations abolish the Thr-Pro PDPK phosphorylation site in the NEFL head domain, which regulates filament assembly via phosphorylation (Pérez-Ollé et al 2005;Sasaki et al 2006). In our study, patients with the Pro22Arg mutation had the same demyelinating neuropathies as did patients with the Pro22Thr mutation; therefore, it seems that the Pro22Arg mutation also may abolish the Thr-Pro phosphorylation site of the head domain by PDPKs.…”
Section: Discussionmentioning
confidence: 92%
“…Neurofilament light chain polypeptide (NEFL), which consists of an N-terminal head, a central road, and a C-terminal tail domain, is one of the most abundant cytoskeletal components in the neuron (Brownlees et al 2002). Several missense mutations in the NEFL gene have been reported, and a number of these have been predicted to produce alterations in the formation of the intermediate filament network in neurons (Pérez-Ollé et al 2005;Sasaki et al 2006). Mutations in the NEFL gene were originally reported to be associated with CMT2E (De Jonghe et al 2001;Fabrizi et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…13 Functional studies have shown that missense mutant NEFL proteins disrupt the assembly with wild-type NEFL and with the NEFM and NEFH, and cause aggregation, resulting in the disruption of axonal neurofilament translocation and anterograde or retrograde axonal transport including mitochondria. [14][15][16] In this study, we found a homozygous nonsense mutation, Glu140-Stop, in one patient (case 2) in addition to four heterozygous missense mutations in five other patients. The parents of case 2 were first cousins, but they never complained of muscle weakness.…”
Section: Discussionmentioning
confidence: 93%
“…The first two CMTassociated NEFL mutations, NFL P8R and NFL Q333P , were identified in respectively a Belgian and a Russian family. In addition to disturb the assembly of NFs, these mutations affect the axonal transport of wild-type and mutant NFs, but also the transport of mitochondria and human amyloid β protein precursor, resulting in alterations of retrograde axonal transport, fragmentation of the Golgi apparatus and increased neuritic degeneration [79,80]. The effect of these mutant proteins on filament assembly was dominant, since wild-type NFL could not rescue the assembly defect.…”
Section: Charcot-marie-tooth Diseasementioning
confidence: 99%
“…These mutations are located throughout the three functional domains of this protein (head, rod and tail) and consist of substitutions, deletions and frame-shift mutations. Co-expression of most NFL mutants with wild-type NFM or NFH subunits disrupted the NF cytoskeleton in vitro, resulting in the formation of aggregates within the cell body [79,80]. The first two CMTassociated NEFL mutations, NFL P8R and NFL Q333P , were identified in respectively a Belgian and a Russian family.…”
Section: Charcot-marie-tooth Diseasementioning
confidence: 99%